Novel bulk synthesis of magnesium oxide nanobelts networks by microwave hydrothermal route - Aal, Nadia Abdel; Al-Ghamdi, Ahmed A.; El-Tantawy, Farid; Yakuphanoğlu, Fahrettin; Farooq, W. A. (Springer, 2014)
Novel magnesium oxide (MgO) nanobelt structures were successfully synthesized on a large scale, low cost and catalyst free by a microwave hydrothermal route using the magnesium metal and potassium hydroxide precursors at 200 A degrees C for 10 min. The synthesized MgO nanobelts were systemically characterized by power X-ray diffraction (XRD), scanning electron microscopy, energy dispersion spectroscopy and transmission-high resolution electron microscopy. The XRD results indicate that the MgO nanobelts have the well-crystalline cubic phase. The detailed morphological studies revealed that the synthesized products were nanobelts and were grown in large quantity. The optical energy gap of MgO nanobelts was found to be 3.1 eV. The photoluminescence spectra of the MgO nanobelts show a strong and broad green emission band, a weak ultraviolet emission band, and a weak red emission band. This novel method will open new dimensions for synthesized 1-D metal oxide and can be easily extended to the synthesis and assembly of other inorganic nanocrystals.
Keywords: MgO nanostructures; XRD; SEM; TEM; Optical